Descriptive Analysis of Graduate Enrollment Trends at Hispanic-Serving Institutions: 2005-2015. (April 2021) - Garcia, Gina A.; Guzman-Alvarez, Alberto
Hispanic-Serving Institutions (HSIs) are postsecondary institutions that enroll 25% Latinx undergraduate students, with little emphasis on graduate enrollment. Graduate enrollment was explored at HSIs, looking at trends over 10 years. Descriptive analyses and data from the Integrated Postsecondary Education Data System (IPEDS) were used, shedding light on enrollment inequities between Latinx undergraduate and graduate students. This study has implications for graduate HSIs, which can become primary educators of a diverse, highly educated future workforce.